EFFECTS OF SHORT AND LONG RUN SUBPRIME CRISIS ON THE INDUSTRIAL SECTOR IN THE EMERGING COUNTRIES: ARDL APPROACH - HELALI, Kamel; REKIK, Mouna; KALAI, Maha (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
This paper deals with the relationship between the 2007 financial crisis and the industrial sector for a panel of six emerging countries over the period 2002-2011. This crisis has spread through several transmission channels and caused many problems in the financial systems and in the economies in general. Any open economy cannot be immune from this crisis. The emerging countries are not isolated from the rest of the world and, as a result, they are affected by the negative effects of the financial crisis because of their interference with the developed economies. The effects are very clear in many real sectors mainly, in the industrial one. Our objective, in this paper, is to study the impact of the subprime crisis on the industrial sector in the emerging countries through the use of the ARDL approach so that we can derive the various short and long-run relationship between the variables question. The estimation results show that recession in the developed economies has reduced industrial production in the emerging countries through the trade channel since it suddenly limited direct investment and threatened the sectors related to the decomposition of the productive process.